Na Reactivity toward Carbonate-Based Electrolytes: The Effect of FEC as Additive. Issue 10 (1st January 2016) - Dugas, R.; Ponrouch, A.; Gachot, G.; David, R.; Palacin, M. R.; Tarascon, J. M.
Abstract : Na-ion batteries have regained attention because they offer sustainability advantages over the Li-ion technology, hence their interest for massive electrochemical storage. Although the Na-ion electrochemistry is analogous to that of the Li-ion concept, there are a few notable differences such as the stability of carbonated-based electrolytes toward the Li or Na metal anodes. Herein we report on the positive effect of FEC as electrolyte additive on the efficiency of Na-half cells which unfortunately comes with a side effect involving the sudden onset of polarization during discharge at unpredictable capacity values. We show that these anomalies, associated to an inefficient plating-stripping at the sodium metal anode, do not appear in full Na-ion cells. Therefore, FEC-based electrolytes are not the panacea and alternative additives must be sought to enable building of reliable half cells with metal anodes.